Überprüfung eines phraseologischen Grundwortschatzes – eine explorative Datenanalyse - Hoffmann, Lea (Kalbotyra, 2020)
This article addresses the question of which possibilities and limitations of frequency-based studies on the relevance of multi-word expressions open up for applied purposes. For this purpose, the corpus Ref10 of the project Wortschatzwissen.de was exploratively examined. After the development of a category system for multi-word expressions, a sample of the corpus was examined and assigned to the different categories. Subsequently, the identified multi-word expressions were compared with a phrase list of Hallsteinsdóttir, Šajánková & Quasthoff (2006). Findings suggest that the proportion of collocations is particularly high in all subcorpora and that, in addition, idioms and light verb constructions are predominant. Moreover, a large proportion of the idioms identified in the Ref10 corpus sample does not occur at all or occurs only partially, i.e. in an unlisted variant, in the phraseological optimum of Hallsteinsdóttir, Šajánková & Quasthoff (2006). This raises above all the question of how phrase variance is to be evaluated in corpus analyses and to what extent corpus linguists should rely only on basic vocabulary from the perspective of Applied linguistics.